Update on the validity of a recipe within chapter 23 of Book XX in Elderly Pliny’s The Natural History - Ene Draghici-Vasilescu, E (ARC Publications, 2022)
In January 2022 I published an article about a particular recipe within chapter 23 of Book XX in Elderly Pliny’s The Natural History. The content of this formula, when ingested, combats asthma. But because I am a historian and a philosopher – hence not a scientist, when I published that piece I did so in order to emphasize that the work of the Naturalist should receive more consideration; I didn’t do it having chiefly in mind technical details. Nevertheless, I had a preliminary hypothesis, thus: if one formula within that collection compiled by the Roman Naturalist is valid, it is very likely that more are so. Therefore, I stated that to verify this, further research to focus on other recipes in The Natural History is needed. This in addition to more tests to be carried on people in order to strongly confirm the formula in the fragment of the work mentioned above; that was my second proposition. Since the publication of the above-mentioned article I learnt that, in fact, some scientific experiments based on the ingredients Pliny mentions have already been successfully conducted, even though the researchers involved in them do not expressly refer to Pliny. I am introducing the results of these assessments in the current text, and I will publish more about them as the research on Pliny’s work advances. I hope that in the light of the information provided here it will become clear why Pliny’s work deserves more scholarly attention than it receives now.